Evaluating trust in mobile banking using DeLone and McLean information systems (IS) success model / Nur Rasyina Rosely - Rosely, Nur Rasyina (2017)
The technology has helped humankind to live such a better life than the past years. A lot of processes can be done quickly, saves money and time. The world that we lived now has improved in almost everything. Banking system has also done a lot of improvements including implementing Internet banking and also mobile banking. Mobile banking continues to gather momentum across developed countries, fueled by rising smartphone use and the steadily improving supply of mobile banking from banks worldwide. Studies shows that number of people using mobile banking is expected to increase. Basically, the objective of this study is to identify the relationship between components of IS Success Model towards Trust and also to identify the influence of user segments (Gender, Age, and Educational Level) towards the relationship between the components of IS Model. Trust in Mobile Banking will be measured by four other variables in the study which are Information Quality, System Quality, Perceived Usefulness, End-User Satisfaction. In other words, constructs that leads to Trust in Mobile Banking consist of four. This study used quantitative approach and the results of the questionnaire were analyzed using IBM SPSS Version 23 statistical tool. There are very few studies that used DeLone and McLean IS Success in Malaysia, especially in mobile banking studies. A set of questionnaire were distributed in UiTM Shah Alam by testing the DeLone and McLean IS Success in a small scope. In order to conduct the study, the researcher used convenience sampling, means anyone who is available to provide the data without having any criteria in order to be the respondent for this study. There are 146 respondents that participated in this study. The outcome may help bank industry to make as a guide to design Trust in Mobile Banking, as well as it will give an insights of the components that leads to Trust based on demographic background. The findings of this study imply that DeLone and McLean IS Success can be used to analyze Trust in Mobile Banking, and it shows that the effect of demographic background such as Gender, Age and Educational Level does not play an important role in Trust in Mobile Banking.